A Cluster and a Search Market CanCoexist - Juha Virrankoski (Aboa Centre for Economics (ACE), 2019)
I examine a rational expectations model of buyers and capacity con-strained sellers, where traders can choose between a cluster and a searchmarket. Sellers choose a market and post a price, and then buyerschoose which market to visit. There is a pure strategy equilibriumwhere all agents are in the cluster. There are also two continua ofmixed strategy equilibria. In a low-price equilibrium the cluster fea-tures overdemand, and in the high-price equilibrium the cluster fea-tures oversupply. The result differs sharply from a model where de-mand is stochastic and realizes after sellers have made their choices.
Keywords: C78; D40; L11; 330; matching; clustering